PEMBUATAN APLIKASI PENJUALAN TANAMAN BERBASIS WEB (E-COMMERCE) MENGGUNAKAN METODE WATERFALL STUDI KASUS TOKO AZRINA FLOWER - COMPUTING INFORMATIKA; Yaya Suharya (Program Studi Teknik Informatika FTI UNIBBA, 2021)
In the business process, Azrina Flower still does it manually, either in marketing or in the process of buying and selling transactions. Limitations Product marketing is an obstacle for stores in increasing sales turnover and weak supervision of goods as well as manual reporting which is a bad impact for stores and is considered less efficient so that sales reports and inventory reports are hampered because of the long process. The purpose of this research is to create an online store website using the waterfall method that can be accessed online. This method is used by researchers to develop software systems by having a software life flow sequentially starting from analysis, design, coding and testing. Web system design (E-commerce) used is wordpress, which is a web developer based on CMS (Content Management System) and is open source which is very popularly used as a blog engine. WordPress is built with the PHP programming language and MySQL database.